2021
DOI: 10.3390/jcm10204710
|View full text |Cite
|
Sign up to set email alerts
|

Acute Coronary Syndromes and Inflammatory Bowel Disease: The Gut–Heart Connection

Abstract: (1) Background: Inflammatory bowel disease (IBD) induces a process of systemic inflammation, sharing common ground with acute coronary syndromes (ACS). Growing evidence points towards a possible association between IBD and an increased risk of ACS, yet the topic is still inconclusive. Therefore, we conducted a systematic review aiming to clarify these gaps in the evidence. (2) Methods: We conducted a systematic search on EMBASE, Cochrane Library, and PubMed, identifying observational studies published prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…A systematic review by Jaaouani et al, had reported that the risk of ACS increases significantly with acute active flares, in addition to prolonged periods of active disease. 6 On the other hand, the risk of ACS is lower in patients who are in F I G U R E 1 Coronary angiography shows thrombus in all three coronary arteries including ramus intermedius. remission phase of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A systematic review by Jaaouani et al, had reported that the risk of ACS increases significantly with acute active flares, in addition to prolonged periods of active disease. 6 On the other hand, the risk of ACS is lower in patients who are in F I G U R E 1 Coronary angiography shows thrombus in all three coronary arteries including ramus intermedius. remission phase of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported in the literature by the various authors. A systematic review by Jaaouani et al, had reported that the risk of ACS increases significantly with acute active flares, in addition to prolonged periods of active disease 6 . On the other hand, the risk of ACS is lower in patients who are in remission phase of the disease 6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study conducted by Jaaouani et al [ 38 ] the use of aminosalicylates, immune modifiers, and biologic therapies did not affect acute coronary syndrome events. However, exposure to anti-TNFs is associated with a decreased risk of acute arterial events in patients with IBD, particularly in men with CD [ 39 ].…”
Section: Risk Factors For Ihd In Ibd Patientsmentioning
confidence: 99%